Pacific code of practice for recruitment of health workers and compendium - World Health Organization ([Geneva] : WHO, 2007)
This code provides guidelines for an ethical approach to the international recruitment of health workers in a manner that takes into account the potential impact of such recruitment on health services in the source country and it seeks to safeguard the rights of recruits, and the conditions relating to their profession in the recruiting countries. [from author]
Keywords: Personnel Selection; Health Workers